The Antibacterial Activity of some Pure Compounds from Diospyros curranii Against some Opportunistic Gram-negative Bacteria - คงเจริญสุนทร, วิสาตรี; เนื่องจำนงค์, วารี; อภิบาล, พนิดา (KKU Science Journal, 2013)
This research was aimed to study effect of cholestanol, stigmasterol and friedelin, derived from the root of Diospyros curranii (Ebenaceae), and compare anti-bacterial activity with two antibiotics; ampicillin and tetracycline against some gram negative opportunistic bacteria. The antibacterial activity of all bioactive compounds were tested against Acinetobacter baumannii, Escherichia coli ATCC 25913 and Pseudomonas aeruginosa. To determine value of Minimal Inhibitory concentration (MIC), the broth dilution susceptibility test was designed to test all pure compounds. The results were indicated that some pure compounds of D. curranii could inhibit the growth of some opportunistic bacteria with the best MICs of 128 µM for stigmasterol. Friedelin could inhibit the growth of E. coli ATCC 25913, A. baumannii and P. aeruginosa with the MIC of 512 256 and 1024 µM friedelin, respectively. Cholestanol could inhibit the growth of P. aeruginosa with the MIC of 2048 µM, but could not inhibit A. baumannii and E. coli ATCC 25913 (MIC more than 2048 µM). When compared antibacterial activity of the compounds to ampicillin and tetracycline, friedelin gave the best antibacterial activity, followed by antibacterial activity of stigmasterol that had antibacterial activity closed to tetracycline. Cholestanol gave antibacterial activity as well as antibacterial activity of ampicillin. In conclusion, some pure compounds from D. curranii could inhibit the growth of bacteria by the different concentrations that correlated to a number of opportunistic bacteria with statistic significance (p<0.05).